Relationship between topography of the residential area of breastfeeding mothers with zinc and calcium level in breast-milk in West Sumatera - Sari, Silvie Permata; Yanwirasti, Yanwirasti; Desmawati, Desmawati (International Journal of Research in Medical Sciences, 2019)
Background: Natural environment, the topography of the residential area affects the nutritional intake of the community greatly. Geographically (including the topography of the residential area), the nutritional intake will affect breastfeeding mothers, because the quantity and quality of breast milk is influenced by the food consumed by mothers every day. Methods: This was observational research with a comparative cross-sectional design. The research was conducted at the Integrated Laboratory of LLDIKTI region X in December 2018 to January 2019 using the Atomic Absorption Spectrophotometer (AAS). Samples were 80 breastfeeding mothers consisting of 40 mothers living in lowland and 40 mothers in Highland. Data analyzed using the Kolmogorov Smirnov normalization test and Mann-Whitney test, if p = 0.05, was considered significant. Results: Research showed that there was a significant relationship between the topography of residential area with zinc (p = 0.00) and calcium levels (p = 0.00). Zinc and calcium levels in breastfeeding mothers were higher in mothers who live in the lowlands than in the highlands. Conclusions: The conclusion of this study, there is a significant relationship between the topography of the residential area of breastfeeding mothers with zinc and calcium levels in breast milk.